Peran Media Sosial Dalam Memengaruhi Krisis Politik Di Indonesia: Kajian Studi Pustaka - Sayyidah Nur Rif'atul Azizah; Dzahwa Salsabila Aulia; Arinza Gusti Maharani; Shella Claudia Shantika; Desy Atika Sari; Khoiriya Ulfah (CV. ITTC INDONESIA, 2026)
This study aims to analyze the role of social media in influencing political crises in Indonesia through a literature review approach. The method used is qualitative research with a library research design that utilizes scientific journals, books, academic articles, and official reports related to social media and Indonesia’s political dynamics. The results of the study indicate that social media has a significant influence on the formation of public opinion, increased political participation, and political communication in the era of digital democracy. Platforms such as Instagram, Facebook, Twitter/X, TikTok, and YouTube serve as the primary means for the rapid and widespread dissemination of political information. However, social media also generates negative impacts in the form of hoaxes, disinformation, political propaganda, polarization, echo chambers, and political buzzer activities that exacerbate political crises. Social media algorithms further reinforce political segmentation and limit the space for public dialogue. On the other hand, social media continues to make a positive contribution to increasing public political participation, particularly among the younger generation. Therefore, it is necessary to strengthen digital literacy, implement adaptive regulations, and foster collaboration between the government, social media platforms, educational institutions, and the public so that social media can be utilized wisely in Indonesia’s democratic life.